Edukasi Pencegahan Perkawinan Anak melalui Pemahaman Hukum Perkawinan Islam dan Hukum Positif bagi Remaja di Desa Soket Dajah Bangkalan - Rodiatus Shofiyah; Atmari; Budi Handayani (BAMALA Institute, 2024)
This community service activity aims to increase public awareness and understanding of the prevention of child marriage through education on Islamic marriage law and positive law in Indonesia. The program was conducted in Soket Dajah Village, Tragah District, Bangkalan Regency, involving adolescents, parents, and community leaders as participants. The activity used an educational and participatory approach through legal counseling, interactive discussions, and question-and-answer sessions. The materials presented included the minimum legal age for marriage according to Law Number 16 of 2019, the principles of marriage in the Compilation of Islamic Law, and the social and legal impacts of child marriage. The results of the activity indicate an increase in participants’ understanding of the legal provisions of marriage and the importance of physical, psychological, and economic readiness before entering into marriage. In addition, the activity encouraged greater legal awareness among adolescents and the community regarding the importance of preventing child marriage. Therefore, community-based legal education can serve as an effective strategy to strengthen public awareness and promote responsible and lawful marriage practices in accordance with Islamic law and national law in Indonesia.